SDS-PAGE of Pseudomonas pseudomallei exotoxins - Jeanne Indriana (Hemera Zoa, 1995)
The protein profiles of Pseudomonas pseudomallei exotoxins which derived from P. pseudomallei strains of different virulence and origin (J53, AN, C2, XI003 and 1328 strains), have been studied by electrophoretic analysis using SDS-PAGE (sodium dodecyl sulphate - polyacrylamide gel electrophoresis).Each of these P. pseudomallei strains is propagated in mucin broth and then incubated statically at 32 ° for 7 days. The exotoxin of each strain has been prepared from that broth culture by centrifugation and followed by ultrafiltration.The result indicated that all of the strains, regardless of its different virulence and origin, showed one protein band common to all, i.e. at a molecular weight of approximately 35 K.